Performance Improving for the Flat Plate Solar Collectors by Using Nanofluids: Review Study - Mohammed A. Abduljleel; Nabil J. Yasin; Safaa A. Ghadhban; Sumair Ahmed Soomro (Journal of Techniques)
In this paper, the literature will be reviewed, and various research works conducted to improve the thermal performance of flat panel solar collectors will be summarized. It will be summarized in more than one way. Firstly, by design using different methodologies and methods to improve the efficiency and the thermal performance of the solar collector by introducing twisted strips that cause increased mixing. Fluids and Friction for FPSCs. To increase heat transfer as well as use porous materials to enhance heat and improve the effectiveness of absorption panels to absorb as much solar radiation as possible as well as thermal insulation methods to reduce losses to surrounding areas. And improve the permeability of the glass cover. Secondly, the use of nanofluids enhances the performance of flat solar collectors instead of the core fluid, and its effect is to improve the thermophysical properties such as thermal conductivity by summarizing previous research using mono nanofluids and hybrid nanofluids. Through studies and research related to the use of mono nanofluids, it was noted that the best nanofluids are those that use CuO and Al₂O₃ particles due to their ease of availability and high thermal conductivity. As for hybrid nanofluids, the best fluids are (CuO + Al₂O₃/water) for the same reason above. As a result of design improvements and the use of nanofluids, temperatures up to (75C°) were obtained.